Polyphasic characterization of heterotrophic bacteria from shrimp farm environments to tetracyclines - Rafael dos Santos Rocha (2016)
Antimicrobial agents of tetracycline class has been extensively used in aquaculture for disease control and growth promotion. Thus, the aim of this study was to evaluate the polyphase profile of the bacterial community in shrimp farming environment front antimicrobial classes of tetracyclines, focusing on Vibrio genus. Water and sediment samples were collected four (4) shrimp farms: two (2) in the state of CearÃ and two (2) in the state of Rio Grande do Norte, of points: estuary, supply channel, pond and drainage channel. Cultivable heterotrophic bacteria (CHB), with resistance to tetracycline (CHB+TET) and oxytetracycline (CHB+OTC), total Vibrio, positive sucrose Vibrio and sucrose negative Vibrio were surveyed by Standard Plate Count method (SPC). The strains isolated from CHB, CHB+TET, CHB+OTC and Vibrio underwent phenotypic identification. The phenotypic profile of antimicrobial susceptibility of strains of Vibrio and other BHC was compared between the disk diffusion techniques and macrodilution by determining the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) for tetracycline and oxytetracycline antimicrobials. Resistance genes tet(M), tet(S) otr(A) and otr(B) were investigated in strains characterized as phenotypically resistant. Diversity of heterotrophic bacteria is influenced by wet and rainy seasons and also by the different collection points within the shrimp farms. Overall, the CHB, CHB+TET and CHB+OTC and Vibrio counts differ between the collection seasons, with higher measurements during the rainy season to the points of pond and drainage channel. 146 strains of CHB, 57 of CHB+TET and 45 of CHB+OTC were isolated, of which the most representative genera were Vibrio and Enterobacter. A total of 100 strains of Vibrio were isolated, which V. coralliilyticus was the most representative species. Antimicrobial profile of Vibrio and other CHB differed between disk-diffusion and macrodilution techniques, being the macrodilution the most efficient in the characterization of resistance among isolates. All strains of Vibrio and other CHB, phenotypically resistant, presented the tet(M) gene as a determinant of resistance determinat, but tet(S) otr(A) and otr(B) genes were not observed. Thus, it proves that Vibrio genus is most abundant among herotrotrophic bacteria with resistance to tetracyclines, with the bacterial diversity strongly influenced by seasons.